FDTD Modeling of Au/Ag Nanoparticles Incorporated Au/Ag Photonic Crystal for Seeking the Maximal Localized Electric Field. Issue 5 (20th February 2022) - Mu, Zhongde; Gu, Hongcheng; Chen, Qiang; Li, Jianqing; He, Xia
Abstract: Photonic crystals (PhC) can be elaborately tailored to enhance the electromagnetic properties of materials and are drawing increasing attention in recent years. However, there is no sufficient theoretical framework to optimize photonic crystal designs for electric enhancement. A comprehensive theoretical model is presented to illustrate Au/Ag photonic crystal enhancement on electric fields and obtain a group of optimal photonic crystal parameters after large number of statistics and parameter scans. The second and deeper layers of PhC only contribute to both 5% extinction and absorption in the far‐field, and there is almost no difference in |E| max among different layers with the coefficient variation at ≈1%. Furthermore, increment of both lattice constants and NP diameters can trigger dramatic changes in |E| max, and the maximal |E| max derived from 190 nm AuNP (nanoparticle)‐Au PhC with the lattice constant of 560 nm. This structure is 47.7, 7.39, 4.63, and 2.69 times that of AuNP incorporated silica wafer, silicon wafer, Ag wafer, and Au wafer, respectively. The strong electric field enhancement attributes to not only the plasmonic effect but also the photonic crystal enhancement effect. The simulation procedures open the possibility of precise photonic crystal structure design and pave the way for various electric field enhancement applications. Abstract : Gold/silver nanoparticle‐photonic crystal hybrid is simulated to enhance localized electric fields. The first layer of photonic crystal contributes over 95% extinction and absorption. Lattice constants and nanoparticle diameters can trigger dramatic changes in the localized electric field. The maximal localized electric field derives from a hybrid of 190 nm diameter gold nanoparticle‐gold photonic crystal with the lattice constant of 560 nm.